Mengakomodasi Praktik Keagamaan di Tempat Kerja: Kasus Pekerja Indonesia di Taiwan: Accommodating Religious Practices in the Workplace: The Case of Indonesian Workers in Taiwan - Rizki Hegia Sampurna (Society, 2019)
The increasing number of Indonesian migrant workers, who are largely Muslims in Taiwan, makes the work environment more diverse. Consequently, the need for diversity management programs such as accommodating religious practices in the workplace has become significantly more relevant. But the extant studies and reports point out those migrant workers, who are largely Muslims, have not been properly accommodated to implement their religious practices in the workplace. The study seeks to understand as how Indonesian migrant workers, who are largely Muslims, experience a kind of deprivation of their religious practices in the workplace. To that end, it uses a qualitative case study method to investigate a group of Indonesian Muslim workers of the X Company who were deprived to observe daily prayers in the workplace. The results of the study evidently found that the employer views that accommodation of such religious practices in the workplace as unreasonable for the company. The results further showed that the accommodation of religious practices of Indonesian Muslim workers was considered as unreasonable because of some important issues such as disruption of job duty, inflexible work schedule, other workers’ concern/objection, facility cost and management response/ approach. Accordingly, the study suggests some recommendations. First, the Taiwanese employer needs to sit together with relevant government institutions and religious leaders to formulate a specific policy on the accommodation of religious practices in the workplace. Second, as a single case study, the results of this study might lack of external validity (generalizability). It therefore strongly suggests prospective researchers to do a cross-cases study of this phenomenon or issue.